Prevalencia de enfermedad renal crónica en los hipertensos seguidos en los centros de salud de España y grado de control de su presión arterial (estudio DISEHTAE)()() - Vara-González, Luis (Aten Primaria, 2008)
OBJECTIVE: To establish what proportion of hypertensive patients being treated in the primary care health centres of Spain have diminished renal function, and to ascertain their level of blood pressure (BP) control. DESIGN: Descriptive, cross-sectional study, based on an external audit of clinical charts. SETTING: Primary care health centres in 14 autonomous regions. PARTICIPANTS: A total of 6113 charts of hypertensive patients from 107 primary care health centres were checked. The selection of primary care health centres and charts was randomized. MAIN MEASUREMENTS: Creatinine and BP figures of the patients included were analyzed. Chronic kidney disease was defined as a glomerular filtration rate (GFR), as calculated by the equation developed by the Modification of Diet in Renal Disease (MDRD) Study, at under 60 mL/min per 1.73 m(2) of body surface area. A good level of BP control was defined as having figures lower than 130/80 mm Hg. RESULTS: Of all patients, 25.7% (95% CI, 24.3-27.2) had a diminished GFR. Of these, 19.1% (95% CI, 16.6-21.9) had a good level of control of systolic BP, 49.9% (95% CI, 46.6-53.2) had a good level of control of diastolic BP, and 15.2% (95% CI, 12.9-17.8) had a good level of control of both. CONCLUSIONS: A considerable proportion of hypertensive patients under treatment in the primary care health centres of Spain have a diminished GFR. Only 1 in 6 of these have their BP under control.